Effectiveness of the Vietnamese Good Agricultural Practice (VietGAP) on plant growth and quality of Choy Sum (Brassica rapa var. Parachinensis) in Northern Vietnam - Tuan M. Ha (Graduate Program of Syiah Kuala University, 2014)
In response to the recent concerns about human health, ecosystem sustainability and thus demands for food safety, production of clean produce, particularly daily-consumed vegetables, is essential. The study was carried out in Thai Nguyen city (northern Vietnam) during August – November 2011 to evaluate impacts of a VietGAP guideline on plant growth and quality of Choy Sum, one of the major vegetables in the research area. The experiment comprised two treatments, a control (local farmers’ conventional practice) and an experimental treatment (plants grown according to the VietGAP guideline). Plant samples of the latter treatment were collected for quality test at the end of the experiment. Results showed that the experimental plants had significant higher growth parameters with regards to leaf areas (7.13 dm2) and average top plant weight (3.33 kg m-2), while those of the control treatment were 5.80 dm2 and 2.77 kg m-2, respectively. Lab test results showed the experimental plant samples met the national quality standards to be certified as a clean product. The participatory on-field experiment would facilitate critical reflections, transformative learning and readiness for adoption of eco-friendly production practices by the local farmers